The Effect of Self-Concept and Creativity on Professional Competence of Paud Teacher in Cakranegara Mataram - Siti Zaenab; Dita DestariIin Rizky Indryani (Jayapangus Press, 2022)
The purpose of this study was to determine: (1) the effect of self-concept on the professional competence of kindergarten teachers in Cakranegara District, NTB (2) the effect of creativity on the professional competence of PAUD teachers in Cakranegara District, NTB (3) the effect of self-concept and creativity together the same as the professional competence of PAUD teachers in Cakranegara District, NTB. By using quantitative methods, this research contains numbers obtained from data and then processed using statistics and then interpreted.